Indonesia Economic Quarterly, October 2016 : Pressures Easing - World Bank (World Bank, Washington, DC, 2016)
This edition of Indonesia Economic Quarterly (IEQ) reports on the key developments over the past three months in Indonesia’s economy, and provides a more in-depth examination of selected economic and policy issues, and analysis of Indonesia’s medium-term development challenges. Global growth was sluggish in the first half of the year, driven by weaker than expected growth in advanced economies. In addition, China’s growth eased as expected as the economy continues to rebalance from investment- to consumption led growth, and as excess industrial capacity is reduced. However, import demand from China was weaker than expected. On the upside, the global financial market volatility leading up to and in the aftermath of the Brexit referendum in June has moderated significantly. Lower volatility in financial markets has contributed to the Rupiah’s stabilization against the US Dollar (in line with most other emerging market currencies). Indonesia’s growth remained resilient in Second Quarter (Q2), partly supported by government expenditure, and is forecast to pick-up gradually on the back of stronger private investment supported by investment climate reforms and credible fiscal policy. This resilience stands in contrast to the performance of several other emerging market commodity exporters.